Development of Guidelines for Adolescent Involvement in Health Research - Warraitch, Azza (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2025)
Adolescent involvement in health research has gained increased recognition over the past two decades, rooted in Article 12 of the UN Convention on the Rights of the Child (UNCRC). Despite this progress, adolescents remain underrepresented in health research due to a lack of awareness and preparedness among researchers on how to meaningfully engage them in research. Existing guidelines on adolescent involvement in health research have significant limitations, resulting in a critical need for more comprehensive and practical guidance for researchers on adolescent involvement in health research. This project aimed to fill this gap by developing a comprehensive set of guidelines for adolescent involvement in health research. To develop these guidelines, I followed the ADAPTE methodology to adapt existing guidelines on adolescent and youth involvement using updated evidence. This guideline development process involved conducting a rapid review, an umbrella review, a qualitative study, and participatory workshops with adolescents and researchers. I actively engaged adolescents as consultants, collaborators, advisors, and co-researchers throughout this guideline development process and evaluated their involvement using a qualitative study. The rapid review aimed to systematically identify all the currently available guidelines on adolescent and youth involvement in health research. I searched six databases for peer-reviewed literature and conducted a grey literature search in two databases, websites of 472 relevant organisations, and sought expert input, resulting in an identification of 88 guidelines. The current guidelines were limited in scope, quality, and content as these often focused narrowly on specific research areas, populations, or user groups, with insufficient stakeholder involvement and limited methodological rigour of development. The guidelines individually lacked comprehensive coverage of recommendations across all topics related to adolescent involvement, highlighting the need for more comprehensive guidelines. The umbrella review aimed to synthesise review-level evidence on adolescent involvement in health research. I searched 11 databases, Google Scholar, PROSPERO, reference lists of eligible reviews, relevant journals, websites of 472 organisations, and sought input from experts, resulting in the inclusion of 99 reviews. The results identified several barriers to adolescent involvement reported by researchers, such as organisational challenges, barriers specific to working with adolescents, and ethical issues such as power dynamics. Adolescents themselves highlighted issues like tokenism, inaccessible processes, and challenges in navigating competing demands. I conducted a qualitative study to explore the strategies to address these barriers to adolescent involvement in health research. Participants included 25 researchers and 25 adolescents, aged 10 to 24 years, from 14 countries. They identified three key strategies: adequate planning for involvement; building relationships; and making involvement engaging. These key themes included a further list of actions and strategies that should be implemented to address the barriers to adolescent involvement. The umbrella review also underscored the numerous benefits of involving adolescents, including enhanced research relevance, better recruitment strategies, improved data collection, and positive impacts on adolescents, such as increased knowledge, skills, and personal development. The review also highlighted examples of meaningful adolescent involvement in planning and conducting the reviews on adolescent and youth involvement in health research included in this umbrella review. These reviews engaged adolescents at most stages of the review process using a wide range of methods, even at technical stages like study selection and data analysis. While adolescent participation was often consultative, there were some examples of more collaborative involvement. The findings highlighted the potential for adolescents’ input to improve the quality and outcomes of evidence syntheses by grounding the process and findings in their experiences and insights. This study also evaluated adolescent coresearchers’ experiences of being involved in this dissertation project by conducting semi-structured interviews with them. Adolescent co-researchers reported to being motivated by opportunities for skill development, career growth, and roles aligned with their interests and highlighted the role of supportive involvement practices in sustaining their involvement. Adolescent co-researchers also reported some positive outcomes from their involvement, including enhanced research knowledge and skills, co - authorship opportunities, financial compensation, and strengthened relationships with the research team. The findings from the above studies were synthesised to develop the initial draft of the guidelines that included 15 chapters. This draft was then reviewed with researchers and adolescents in participatory workshops to seek their input on the content of the guidelines, develop case studies that illustrate the outlined principles in practice, and address any limitations and gaps to ensure the guidelines are practical, relevant, and applicable across diverse contexts. The resulting guidelines provide actionable recommendations for researchers and practitioners on critical aspects of adolescent involvement, such as preparation for adolescent involvement, ethical considerations, recruitment, retention, and engagement methods. These guidelines provide a useful resource for researchers and practitioners aiming to enhance the quality and impact of adolescent health research.
APPROVED
Keywords: youth; adolescents; young people; participatory; engagement; involvement; health research; guidelines